Search for Pair-Produced Resonances Each Decaying into at Least Four Quarks in Proton-Proton Collisions at √s=13 TeV; Physical Review Letters; Vol. 121, iss. 14 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Baydali S. A. Sergey Anatolievich (2018, 2018)
Title screen